The Spiral And The Meanders Motives In Petroglyphs Associated To Pre-Columbian Hydraulic Architecture Of The Caribbean Costa Rica - Arce Cerdas, Marco (2019)
This paper presents the results of recent investigations carried out in the Rosa Maria archaeological site (C-29 RM) and in the Guayabo National Monument (C-365 MNG), which reveal a direct link between certain representations made on rocks (petroglyphs) and some ancient hydraulic structures. Thus, it provides a methodological approach based on field data recolection and its spatial analysis that enable to prove the association of certain motives and its location on those ancient engineering structures. With this in mind, the article discusses and establish context interpretations about (1) their possible meaning/interpretation and (2) the function of those engravings, this according to direct scientific data obtained product of the study of Pre-Columbian Costa Rica´s water management practices and architecture.